1998
DOI: 10.1080/0742-969x.1998.11882905
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management Issues: The Cost of Medications in Rural Settings

Abstract: Cost of analgesic and adjuvant medications used by rural patients with cancer cared for by 29 nurses participating in an in-depth education program were evaluated before and after the program. Across all time periods, the median daily cost was $5.16 across all medications. Average daily cost and maximum and median cost of all medications were $5.36, $74.38 and $3.58, respectively. Average daily cost did not change over time. Average pain intensity did not change over time and was not related to prescribing pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Though analyses to date have recognized cost as an important factor, 6 the cost of pain management has only been addressed in program evaluation 7 and scattered evaluations in individual settings. [8][9][10] One study examined the cost of analgesic and adjuvant medications used by rural patients with cancer. It was found that neither average daily cost nor average pain intensity changed over time, and pain intensity was not related to prescribing patterns or daily costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though analyses to date have recognized cost as an important factor, 6 the cost of pain management has only been addressed in program evaluation 7 and scattered evaluations in individual settings. [8][9][10] One study examined the cost of analgesic and adjuvant medications used by rural patients with cancer. It was found that neither average daily cost nor average pain intensity changed over time, and pain intensity was not related to prescribing patterns or daily costs.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that neither average daily cost nor average pain intensity changed over time, and pain intensity was not related to prescribing patterns or daily costs. 9 Another study assessed the cost of autologous bone marrow harvesting in outpatients. Actual costs in the outpatient setting were 74% of modeled inpatient costs.…”
Section: Introductionmentioning
confidence: 99%
“…The cancer pain management literature is focused on standards for assessment and management and on the identification of barriers to effective care. These barriers include provider lack of knowledge and attitudinal biases, fear and misconceptions of patients and families, and regulatory issues 2–8 . However, the degree of influence of a particular barrier varies by the type of setting, making it necessary to diagnose individual issues and target strategies for improvement.…”
mentioning
confidence: 99%